Symposium 7: Recurrent routines in the classroom madness: pushing patterns past the design phase - Prieto, Luis Pablo; Villagrá-Sobrino, Sara; Dimitriadis, Yannis; Jorrín-Abellán, Iván M.; Martínez-Monés, Alejandra; Anguita-Martínez, Rocío (Proceedings of the International Conference on Networked Learning, 2010)
The notion of pedagogical patterns has proved very useful in the field of learning design, especially with regard to activities for complex educational scenarios, such as computer-supported collaborative learning (CSCL). However, CSCL designs (pattern-based or not) also have to be enacted by teachers, and very often ambiguities, difficulties and deviations arise in this enactment. This paper reports recent experiences in an authentic primary school setting, aimed to study teachers who are not technology experts, designing, enacting and even improvising with a CSCL tool. This study uncovered a set of recurrent routines in the design of activity scripts (which we could see as implicit design patterns), as well as a limited set of routines in the enactment of these activities. The comparison of the designs and their enacted counterparts revealed that the designed routines were completed with additional sets of unexpected routines, bridging the gap between high-level designs and the concrete classroom performance. This paper discusses the idea of eliciting an extensible set of enactment patterns/routines and the level of formalization needed, especially regarding its potential usefulness as a tool (mediating artifact) to support practitioners in enacting CSCL activities in a more flexible and effective way.